2021
DOI: 10.13187/ijmil.2021.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Communication Barriers and Process of Feedback in Social Interactions

Abstract: Barriers in a communication process hinder the intended feedback which, if not sent back to the message sender, disperse in the surrounding. This study intends to relate those communication barriers with the message-receiver, who instead of sharing his or her views back to the messagesender, contends to disseminate it among peer groups and social media platforms. The study conducted in-depth interviews of 9 students who were scrutinized as message receivers in their communication roles of parents-children, tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Not surprisingly, scholars are interested in analyzing communication barriers (i.e. cultural, psychological, educational, economic, and religious ones) and process of feedback in social interactions (Hassan et al, 2021) and the problem of teenage extremism as a form of social deviation in the configuration of modern media texts in the transformation processes (Gorbatkova, 2021). To continue the discourse on the younger generation, it is also necessary to mention a very ingenious study of the effects of raids on restaurants shown in crime or investigation shows of Pakistan on the behaviors of youth (Awais, Ali, 2022).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Not surprisingly, scholars are interested in analyzing communication barriers (i.e. cultural, psychological, educational, economic, and religious ones) and process of feedback in social interactions (Hassan et al, 2021) and the problem of teenage extremism as a form of social deviation in the configuration of modern media texts in the transformation processes (Gorbatkova, 2021). To continue the discourse on the younger generation, it is also necessary to mention a very ingenious study of the effects of raids on restaurants shown in crime or investigation shows of Pakistan on the behaviors of youth (Awais, Ali, 2022).…”
Section: Discussion and Resultsmentioning
confidence: 99%